Tan(x + pi) - cos (x + pi/2) =0

[Tan(x)+Tan(pi)]/(1 - tan(x)tan(pi)] - [ cos(x)cos(pi) - sin(x)sin(pi/2) ] = 0

[tan(x) + 0]/(1 - tan(x)(0)] - [ cos(x)(0) - sin(x)(1)] = 0

tan(x) + sin(x) = 0

tan(x) = -sin(x)

sin(x)/cos(x) = -sin(x)

sin(x) = -sin(x)cos(x)

sin(x) + sin(x)cos(x) = 0

sin(x)[1 + cos(x)] = 0

sin(x) = 0, 1 + cos(x) = 0

x =0 cos(x) = -1

x = pi

sin(x)/cos(x) = -sin(x)

sin(x) = -sin(x)cos(x)

sin(x) + sin(x)cos(x) = 0

sin(x)[1 + cos(x)] = 0

sin(x) = 0, 1 + cos(x) = 0

x =0 cos(x) = -1

x = pi

## No comments:

## Post a Comment